Determinants of Stock Returns with Dividend Policy as a Moderating Variable in Consumer Goods Companies - Monang Juanda Tua Sihombing; Sri Trianovie (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study investigates the determinants of stock returns with dividend policy as a moderating variable in consumer goods companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative approach was employed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with Smart PLS software. The sample consisted of 61 consumer goods companies selected through purposive sampling. The results indicate that net profit margin has no significant effect on stock returns, suggesting that profitability does not necessarily influence investor decisions in this sector. Inflation, however, shows a positive and significant effect on stock returns, highlighting that inflationary changes encourage investors to adjust their investment strategies. In contrast, the Bank Indonesia interest rate does not significantly affect stock returns, implying that interest rate fluctuations are not a primary factor for investors in consumer goods companies. Furthermore, the residual test demonstrates that dividend policy, measured by the dividend payout ratio, does not moderate the relationships between financial ratios, macroeconomic variables, and stock returns. These findings imply that dividend distribution alone does not guarantee investor interest, as investors tend to prioritize fundamental and long-term company performance over short-term payouts. The study contributes to the literature on stock return determinants by integrating firm level profitability and macroeconomic conditions with dividend policy as a moderating factor. It also provides practical insights for investors and managers, particularly regarding the limited role of dividend policy in influencing investment behavior in the Indonesian consumer goods sector.